Rate of Solute Incorporation to Liposomes Evaluated from Encapsulated Enzymes Activities - Lissi-Gervaso, E; Calderon-Espinoza, C; Calderon-Espinoza, C; Ahumada-Escandon, M; Ahumada-Escandon, M (2014)
There are numerous studies on systems comprising an enzyme encapsulated in unilamellar liposomes and its substrate initially present in the external aqueous media. Most of these studies are focused on enzyme stability and activity in a restricted media. However, the rate of the process is also determined by the capacity of the substrate to permeate towards the liposome inner pool. In spite of this, there are few studies aimed at a quantitative evaluation of the substrate permeation rate and its lifetime inside the liposome pool. In the present work, we describe, in terms of a very simple mechanism, the permeation of glucose and hydrogen peroxide in DPPC unilamellar liposomes. To this aim, we evaluated the rate of the process employing encapsulated glucose oxidase and catalase in the kinetic diffusion controlled limit. Under this condition, the rate of the process becomes zero order in the enzyme and allows a direct evaluation of the rate constant for the permeation process and the lifetime of a substrate molecule incorporated into the liposome inner pool. © 2014 International Union for Pure and Applied Biophysics (IUPAB) and Springer-Verlag Berlin Heidelberg.